"Here Be Dragons:" The Tyranny of the Cityscape in James Baldwin's Intimate Cartographies. (29th September 2015) - Cleary, Emma
Abstract : The skyline of New York projects a dominant presence in the works of James Baldwin—even those set elsewhere. This essay analyzes the socio-spatial relationships and cognitive maps delineated in Baldwin's writing, and suggests that some of the most compelling and intense portrayals of New York's psychogeographic landscape vibrate Baldwin's text. In The Price of the Ticket (1985), Baldwin's highly personalized accounts of growing up in Harlem and living in New York map the socio-spatial relationships at play in domestic, street, and blended urban spaces, particularly in the title essay, "Dark Days, " and "Here Be Dragons." Baldwin's third novel, Another Country (1962), outlines a multistriated vision of New York City; its occupants traverse the cold urban territory and struggle beneath the jagged silhouette of skyscrapers. This essay examines the ways in which Baldwin composes the urban scene in these works through complex image schemas and intricate geometries, the city's levels, planes, and perspectives directing the movements of its citizens. Further, I argue that Baldwin's dynamic use of visual rhythms, light, and sound in his depiction of black life in the city, creates a vivid cartography of New York's psychogeographic terrain. This essay connects Baldwin's mappings of Harlem to an imbricated visual and sonic conception of urban subjectivity, that is, how the subject is constructed through a simultaneous and synaesthetic visual/scopic and aural/sonic relation to the city, with a focus on the movement of the body through city space.